Pengaruh Keterlibatan Suplier Dan Konsumen Serta Inovasi Produk Terhadap Performa Produk Baru Di Pt. Puspa Pharma - Rey Hagai Yheri dan Yanuar (Universitas Tarumanagara, 2019)
This study aims to find out how the influence of several factors studied on the performance of new products so that the advantages and disadvantages of PT. Puspa Pharma. Some of these factors are the suppression of brand profiles, internal coordination, competitor-oriented, product innovation, and the involvement of consumers and suppliers. The data used in this study are primary data, which came from the results of questionnaire collection as many as 96 respondents at PT. Puspa Pharma. This research takes place from March 2018 to November 2018. The data analysis method used in this study is the Partial Least Square (PLS) analysis method that uses SmartPLS software version 3.0. The results of the study show that the performance of new products at PT. Puspa Pharma is more influenced by the involvement of suppliers and consumers compared to product innovation. Where the involvement of suppliers and consumers is supported by two important factors namely competitor-oriented and product innovation itself. Whereas internal coordination and suppression of brand profiles do not affect the involvement of suppliers and consumers.